2022
DOI: 10.1128/mbio.02441-21
|View full text |Cite
|
Sign up to set email alerts
|

A Filamentous Bacteriophage Protein Inhibits Type IV Pili To Prevent Superinfection of Pseudomonas aeruginosa

Abstract: Pf bacteriophage (phage) are filamentous viruses that infect Pseudomonas aeruginosa and enhance its virulence potential. Pf virions can lyse and kill P. aeruginosa through superinfection, which occurs when an already infected cell is infected by the same or similar phage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 61 publications
1
53
0
Order By: Relevance
“…In our case, we discovered that conditioned media from phage producers inhibits phage infection. While superinfection immunity due to intracellular phage proteins has been reported in many systems (sieB of Salmonella phage P22 and E. coli phage lambda 49 , pIII of E. coli phage M13 51 , PfsE of Pseudomonas phage Pf 50 ), to the best of our knowledge, this is the first example of extracellular release of a phage protein to modulate immunity against self. Although mechanistically dissimilar, it is reminiscent of immune evasion by respiratory syncytial virus mediated by its extracellular soluble G protein 78,79 , suggesting that yet another mammalian immune system feature may have a prokaryotic counterpart 80 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our case, we discovered that conditioned media from phage producers inhibits phage infection. While superinfection immunity due to intracellular phage proteins has been reported in many systems (sieB of Salmonella phage P22 and E. coli phage lambda 49 , pIII of E. coli phage M13 51 , PfsE of Pseudomonas phage Pf 50 ), to the best of our knowledge, this is the first example of extracellular release of a phage protein to modulate immunity against self. Although mechanistically dissimilar, it is reminiscent of immune evasion by respiratory syncytial virus mediated by its extracellular soluble G protein 78,79 , suggesting that yet another mammalian immune system feature may have a prokaryotic counterpart 80 .…”
Section: Discussionmentioning
confidence: 81%
“…There are examples of superinfection inhibition where an intracellular bacteriophage protein does not allow new phage infections 49,50 . In fact, gIII expression from the M13 bacteriophage is known to prevent the entry of a new phage into its host 51,52 , a result that we were able to confirm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prophages often express genes that provide competitive advantages to their host, including genes involved in bacterial pathogenicity [ 74 , 75 , 76 ] or virulence factors [ 77 , 78 , 79 , 80 , 81 , 82 ]. Prophages also have various mechanisms to prevent infection by other phages [ 83 , 84 , 85 , 86 ]. However, the role of phages in the spread of ARGs remains controversial.…”
Section: Lytic and Lysogenic Phages Contribute To Amrmentioning
confidence: 99%
“…We recently reported that bacteriophage vB_PaeP_CMS1 does not utilize type IV pili as a receptor during infection of Pseudomonas aeruginosa ( 1 ). Here, we announce the genome sequence of the vB_PaeP_CMS1 bacteriophage.…”
Section: Announcementmentioning
confidence: 99%